2013
DOI: 10.5267/j.msl.2013.04.028
|View full text |Cite
|
Sign up to set email alerts
|

A survey on the impact of the training period on empowering management team: A case study Saipa Group

Abstract: Having reliable and skilled employees are essential component of any organization. Employees are considered as intangible assets for most organizations and they are the primary source of making value added decisions. On the other hand, a learning organization is capable of making continuous improvement and survives in today’s competitive environment. The proposed study of this paper considers whether training programs could empower employees who were working as managers for Saipa Group Company, a well-known au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…Arabshahi et al (2013) examined the effect of organizational intelligence on faculty members' knowledge sharing behaviors and reported that there was a significant relationship between organizational intelligence and faculty members' knowledge sharing behaviors. Eyvazi et al (2013) investigated the effects of human resource management on empowering employees in banking industry and reported that empowering employees could increase organizational commitment and Darvish et al (2013) confirmed the same results on other industry. Shirvani et al (2013) presented an empirical investigation to investigate the relationship between job satisfaction and employees' personal characteristics including gender, marital status, etc.…”
Section: Introductionsupporting
confidence: 52%
“…Arabshahi et al (2013) examined the effect of organizational intelligence on faculty members' knowledge sharing behaviors and reported that there was a significant relationship between organizational intelligence and faculty members' knowledge sharing behaviors. Eyvazi et al (2013) investigated the effects of human resource management on empowering employees in banking industry and reported that empowering employees could increase organizational commitment and Darvish et al (2013) confirmed the same results on other industry. Shirvani et al (2013) presented an empirical investigation to investigate the relationship between job satisfaction and employees' personal characteristics including gender, marital status, etc.…”
Section: Introductionsupporting
confidence: 52%
“…Empowerment changes the organizational culture to reduce the conflict between the objectives of organizations and individuals (Petter, et al, 2000cited in Baird, 2006. According to Darvish et al (2013), training programs may increase employees' self-organization as well as efficacy characteristics. Khani et al (2013) stated that spiritual leadership could also influence significantly on empowering employees.…”
Section: Introductionmentioning
confidence: 99%
“…During the past few years, there have been many studies on the effects of HRM on the success of business units. Darvish et al (2013) investigated whether training programs could empower employees who were working as managers for Saipa Group Company, a well-known automaker in Iran. The study focused on those employees who attended in master program in one of educational organizations in city of Tehran, Iran.…”
Section: Introductionmentioning
confidence: 99%